2021
DOI: 10.1186/s12966-021-01125-8
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the 2008 Great Recession on dietary intake: a systematic review and meta-analysis

Abstract: Background The 2008 Great Recession significantly impacted economies and individuals globally, with potential impacts on food systems and dietary intake. We systematically reviewed evidence on the impact of the Great Recession on individuals’ dietary intake globally and whether disadvantaged individuals were disproportionately affected. Methods We searched seven databases and relevant grey literature through June 2020. Longitudinal quantitative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
(322 reference statements)
1
16
0
Order By: Relevance
“…The study also revealed that vegetables and dairy consumption in Hubei Province was lower than recommended. Our partial results are similar to a systematic review indicating that the great recession of 2008 caused a decrease in consumptions of foods such as fruit and vegetable ( 35 ). Two studies ( 36 , 37 ) conducted in the Navajo nation found that access to and availability of foods are particularly important and determine food consumption.…”
Section: Discussionsupporting
confidence: 88%
“…The study also revealed that vegetables and dairy consumption in Hubei Province was lower than recommended. Our partial results are similar to a systematic review indicating that the great recession of 2008 caused a decrease in consumptions of foods such as fruit and vegetable ( 35 ). Two studies ( 36 , 37 ) conducted in the Navajo nation found that access to and availability of foods are particularly important and determine food consumption.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, while some reviews considered a broad range of health outcomes in their review, 12 13 other reviews focused on specific health outcomes such as mental health, 14–16 infectious diseases 17 and dietary intake. 18 Specifically, of the 21 reviews, 13 examined the link between the economic crisis and aspects concerning mental health (eg, depression, suicide), 4 reviews reported findings on infectious disease outcomes, 6 reviews looked at health behaviours (eg, alcohol consumption) and 2 reviews focused on cardiovascular disorders. The key mechanisms to explain the association between the impacts of the economic crisis on health include austerity measures along with cuts in social welfare and unemployment.…”
Section: Resultsmentioning
confidence: 99%
“… 25 The economic crisis was also associated with inequalities in dietary intake. 18 22 According to Jenkins et al, 18 calorie intake decreased in high-income countries but increased in middle-income countries. The authors also found that fruit and vegetable consumption decreased, specifically among disadvantaged groups (eg, women without educational qualifications).…”
Section: Resultsmentioning
confidence: 99%
“…This weight gain tends to occur in families with low economic income. They tend to choose foods high in carbohydrates and fat (high carbo-high fat) with relatively affordable prices [26]. Basic Health Survey (Riskesdas) 2018 showed that 95.5% of Indonesian people >5 years old had consumed fewer fruits and vegetables [27].…”
Section: Lifestyle and Food Pattern Changesmentioning
confidence: 99%